2018
DOI: 10.4103/aer.aer_227_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levobupivacaine and levobupivacaine with dexmedetomidine in infraumbilical surgeries under spinal anesthesia

Abstract: Introduction:Spinal anesthesia is a widely used technique providing faster onset with effective and uniformly distributed sensory and motor block. Due to decreased cardiovascular and central nervous system toxicity, levobupivacaine is a good alternative for spinal anesthesia. Dexmedetomidine when used intrathecally is associated with prolonged motor and sensory block, hemodynamic stability, and less requirement of rescue analgesia in 24 h.Materials and Methods:A prospective, randomized study was carried out wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our searches retrieved 1,206 citations and after removal of duplicates, there were 674 unique citations. After review, a total of 24 RCTs met our selection criteria and were included in the final analysis (Attri, Bansal, Chatrath, Kaur, & Khetarpal, 2015;Chatterji, Gupta, Sharma, & Chatterji, 2017;Ganesh & Krishnamurthy, 2018;Gautam, Lama, & Sharma, 2018;Gupta et al, 2011;Kataria, Jarewal, Kumar, & Kashyap, 2018;Li et al, 2015;Mahendru et al, 2013;Mohamed, Fares, & Mohamed, 2012;Munnoli et al, 2016;Naaz, Bandey, Ozair, & Asghar, 2016;Nethra et al,…”
Section: Additional Analyses and Risk Of Bias Across Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Our searches retrieved 1,206 citations and after removal of duplicates, there were 674 unique citations. After review, a total of 24 RCTs met our selection criteria and were included in the final analysis (Attri, Bansal, Chatrath, Kaur, & Khetarpal, 2015;Chatterji, Gupta, Sharma, & Chatterji, 2017;Ganesh & Krishnamurthy, 2018;Gautam, Lama, & Sharma, 2018;Gupta et al, 2011;Kataria, Jarewal, Kumar, & Kashyap, 2018;Li et al, 2015;Mahendru et al, 2013;Mohamed, Fares, & Mohamed, 2012;Munnoli et al, 2016;Naaz, Bandey, Ozair, & Asghar, 2016;Nethra et al,…”
Section: Additional Analyses and Risk Of Bias Across Studiesmentioning
confidence: 99%
“…Eight studies provided data on this outcome (Figure 3) (Attri et al, 2015;Gautam et al, 2018;Kataria et al, 2018;Mohamed et al, 2012;Munnoli et al, 2016;Naaz et al, 2016;Patro et al, 2016;Rahimzadeh et al, 2018). The MD in pain scores was substantially heterogeneous (I 2 > 94%) at 6, 12 and 24 postoperative hours.…”
Section: Postoperative Pain Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its quick initiation and longer duration of sensory block, shorter duration of motor block, and reduced cardiac toxicity, levobupivacaine is a preferable local anaesthetic when compared to bupivacaine ( 16 ). Previous research indicated that combining dexmedetomidine with levobupivacaine generates efficient analgesia, extends duration of motor and sensory block, and offer superior postoperative analgesia with less detrimental effects ( 17 ).…”
Section: Discussionmentioning
confidence: 99%